A need to increase von Willebrand disease awareness: vwdtest.com – A global initiative to help address this gap. (March 2023) - Corrales-Medina, Fernando F.; Federici, Augusto B.; Srivastava, Alok; Dougall, Alison; Millar, Carolyn M.; Roberts, Jonathan C.; Jaffray, Julie; Berntorp, Erik
Abstract: Von Willebrand disease (VWD) is an inherited bleeding disorder caused by quantitative or qualitative deficiencies in von Willebrand factor (VWF). People with VWD may experience excessive, recurrent or prolonged bleeding, particularly during menstruation, childbirth, surgery or following trauma. However, many VWD patients are undiagnosed, and therefore inadequately treated. Reasons for the underdiagnosis of VWD include its relatively mild symptoms, complex diagnosis, lack of awareness among non-specialist healthcare providers and the general population, and a lack of prioritisation of disorders disproportionately affecting females. The vwdtest.com platform was launched as part of a global initiative to raise awareness and improve diagnosis of VWD. Besides providing VWD-specific educational resources, the website includes an online bleeding self-assessment tool and offers diagnostic support for individuals, and their providers, who have a score suggestive of a bleeding disorder. vwdtest.com helps to address these unmet needs, especially in regions with limited access to educational and diagnostic resources.